(untitled) (Palíndromo, 2026)
We examine the possibility of conceptualizing the category of the sublime in the work of the contemporary artist Robert Smithson. The notion of the modern sublime emerged in Europe in the 18th century within Enlightenment philosophy and German Romanticism, and was subsequently reformulated in the twentieth century by thinkers such as Jean-François Lyotard and Fredric Jameson. Smithson’s oeuvre reflects critically on the relationship between humanity and nature. By proposing a reconceptualization of nature, landscape, and the art object itself, his works mobilize diverse media and supports, assuming a process-based character and incorporating multiple temporalities. His large-scale public works, such as Spiral Jetty, elicit in the viewer a sense of awe, prompting an inquiry into the possibility of articulating a contemporary sublime within his artistic production.